Tandem Orthotopic Living Donor Liver Transplantation Followed by Same Donor Haploidentical Hematopoietic Stem Cell Transplantation for DOCK8 Deficiency. Issue 10 (October 2019) - Freeman, Alexandra F.; Yazigi, Nada; Shah, Nirali N.; Kleiner, David E.; Parta, Mark; Atkinson, Prescott; Heller, Theo; Holland, Steven M.; Kaufman, Stuart S.; Khan, Khalid M.; Hickstein, Dennis D.
Abstract : Background: An 11-year-old girl with dedicator of cytokinesis 8 (DOCK8) deficiency was proposed for potentially curative hematopoietic stem cell transplantation (HSCT), the donor being her haploidentical mother. However, end-stage liver disease caused by chronic Cryptosporidium infection required liver transplantation before HSCT. Methods: Consequently, a staged approach of a sequential liver transplant followed by a HSCT was planned with her mother as the donor for both liver and HSCT. Results: The patient successfully underwent a left-lobe orthotopic liver transplant; however, she developed a biliary leak delaying the HSCT. Notably, the recipient demonstrated 3% donor lymphocyte chimerism in her peripheral blood immediately before HSCT. Haploidentical-related donor HSCT performed 2 months after liver transplantation was complicated by the development of acyclovir-resistant herpes simplex virus viremia, primary graft failure, and sinusoidal obstruction syndrome. The patient died from sinusoidal obstruction syndrome–associated multiorgan failure with Candida sepsis on day +40 following HSCT. Conclusions: We discuss the many considerations inherent to planning for HSCT preceded by liver transplant in patients with primary immunodeficiencies, including the role of prolonged immunosuppression and the risk of infection before immune reconstitution. We also discuss the implications of potential recipient sensitization against donor stem cells precipitated by exposure of the recipient to the donor lymphocytes from the transplanted organ.